Towards the Critical Edition of the Rutbat al-ḥakīm: A Few Preliminary Observations - Callataÿ, Godefroid de (Arabica, 2015)
This article is focused on the manuscript tradition of the Rutbat al-ḥakīm, an alchemical treatise written in al-Andalus by Maslama b. Qāsim al-Qurṭubī in 339/950-342/953. The authors also describe new manuscripts of the work, including one among the earliest in the tradition of the Rutba, remained unknown until now. At the end of the article, new elements are provided about the dating of the Rutba as found in manuscripts.